Pediatric SMA patients with complex spinal anatomy: Implementation and evaluation of a decision-tree algorithm for administration of nusinersen. (March 2021) - Carrera-García, Laura; Muchart, Jordi; Lazaro, Juan José; Expósito-Escudero, Jessica; Cuadras, Daniel; Medina, Julita; Bosch de Basea, Magda; Colomer, Jaume; Jimenez-Mallebrera, Cecilia; Ortez, Carlos; Natera-de Benito, Daniel; Nascimento, Andrés
Abstract: The approval of nusinersen for the treatment of spinal muscular atrophy (SMA) has significantly changed the natural history of the disease. Nevertheless, scoliosis secondary to axial muscle weakness occurs at some point in most of patients with SMA and a conventional posterior interlaminar approach for intrathecal administration of nusinersen can be particularly challenging to perform in patients with severe scoliosis and/or previous spine fusion surgeries. We developed a protocol for the administration of nusinersen in pediatric patients, which includes a decision-tree algorithm that categorizes patients according to the estimated technical difficulty for the intrathecal administration. Complex spine patients were defined as those with a Cobb angle greater than 50° and/or a history of spinal surgery, while the rest of patients were considered non-complex. Nusinersen was successfully administered through a conventional non-CT-guided lumbar puncture in all 14 non-complex spine patients (110 out of 110 procedures; 100%). The feasibility of the intrathecal injection in the 15 complex spine patients was assessed by 3D CT. Administration was considered unfeasible in 7 out of these 15 patients according to imaging. In the 8 complex spine patients in whom the administration was considered feasible, conventional non-CT-guided lumbar punctures were successful only in 19 out of 53 procedures (36%). The remaining 34 procedures (64%) were guided by CT scan, all successful. Our work demonstrates that a cut-off point of 50° in Cobb angle and history of spinal surgery can reliably be used to anticipate the need for CT guidance in nusinersen administration. Graphical abstract: Image 1 Highlights: We propose a protocol for nusinersen administration with a decision-tree algorithm. Image-guided lumbar punctures were performed following a low-dose imaging protocol. The protocol proved to be feasible and safe in a large cohort of pediatric patients. A 100% success rate was achieved and serious adverse effects were rare. The algorithm can be used to make treatment decisions about complex spine patients.